Scrutinizing Learning Management Systems in Practice: An Applied Time Series Research in Higher Education - Barut Tuğtekin, Esra (International Review of Research in Open and Distributed Learning, 2023)
This study examined the use of Advancity Learning Management Systems (ALMS) and the Moodle Learning Management Systems (LMS) in learning settings, as well as online exams, within the framework of Transactional Distance Theory. With 146 college students (nfemale = 102, nmale = 44) as voluntary participants, data was gathered through an online questionnaire. A time series design was used for two different LMS sessions, and participants who voluntarily participated in ALMS and Moodle LMS sessions were matched. The findings revealed that while Moodle and ALMS both receive relatively similar assessment ratings for online exams, Moodle scored better in terms of learning setting. When factors of the Learning Management Systems Evaluation Scale (LMSES) based on Transactional Distance Theory were compared, the dialogue and autonomy factors were significantly higher for Moodle LMS than for ALMS. When online exams in the LMS were compared, there was no significant difference between ALMS and Moodle LMS, and for both LMS, the reliability factor was a determinant indicator than the other factors. As a result, in assessing and using an LMS, choices should be based on how well the LMS characteristics address an institution’s demands.